EFFECTS OF DIETARY SUPPLEMENTATION OF SYNBIOTICS ON GROWTH, INTESTINAL BARRIER FUNCTION AND CECAL MICROORGANISMS OF CHERRY VALLEY DUCKS - R. X. Wang; Z. W. Chen; R. Chen; Q. Liu; S. Zhuang (Journal of Animal and Plant Sciences, 2022)
The present study was set out to explore the effects of diets supplemented with synbiotics, as a possible antibiotic substitute, on growth performance, intestinal barrier function and cecal microorganisms of Cherry Valley ducks. Briefly, a total of 540 Cherry Valley ducks (one-day-old) were randomly categorized into 3 groups for 42 days: control group (basal diets free from the antibiotic), antibiotic group (basal diets supplemented with 40 mg/kg bacitracin zinc), and synbiotic group (basal diets supplemented with 1 000 mg/kg synbiotic). Each group consisted of 6 replicates of 30 ducks each. In synbiotic group, average-day-gain (ADG) throughout the trial period (p<0.05) and average-day-feed-intake (ADFI) during the starter and grower periods (p<0.05) were increased as compared with the control group. Moreover, dietary synbiotics enhanced ileal villus height to crypt depth (V/C), decreased ileal crypt depth compared with the control group (p<0.05). In addition, the synbiotics increased numbers of Intraepithelial lymphocytes (IELs) and goblet cells in the small intestine(p<0.05), and secretory IgA (sIgA) concentration in the duodenum and jejunum (p<0.05) of 42-day-old ducks as compared with the control group. Furthermore, synbiotics supplementation increased the mRNA expression of jejunal mucosal occluding (OCLN) and the population of Bifidobacterium in cecal chyme (p<0.05). In conclusion, diets supplemented with synbiotics could improve growth performance and intestinal morphology, enhance intestinal barrier function, and modulate the cecal microorganisms in Cherry Valley ducks.
Keywords: synbiotic; Cherry Valley ducks; growth performance; intestinal barrier function; cecal microorganisms